2020
DOI: 10.1111/age.12971
|View full text |Cite
|
Sign up to set email alerts
|

An integration analysis based on genomic, transcriptomic and QTX information reveals credible candidate genes for fat‐related traits in pigs

Abstract: Summary Meat quality improvement is of great interest to researchers in pig breeding and many researchers have identified abundant associated quantitative trait loci, genes and polymorphisms (QTXs) for fat‐related traits. However, it is challenging to determine credible candidate genes from a mass of associations. The efficiency of identification of credible candidate genes in these QTXs is restricted by limited integration analyses of data from multiple omics. In this study, we constructed a ‘candidate gene m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…FoxO1 promotes lipogenesis during porcine intramuscular preadipocyte differentiation by downregulating PDGFRα (Sun et al, 2017). A previous study showed that the PPARα gene is related to pig fat traits by incorporating transcriptome and genomic data (Fu et al, 2020). The downregulation of CPT2 can induce the suppression of fatty acid β‐oxidation to increase IMF accumulation (Fujiwara et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…FoxO1 promotes lipogenesis during porcine intramuscular preadipocyte differentiation by downregulating PDGFRα (Sun et al, 2017). A previous study showed that the PPARα gene is related to pig fat traits by incorporating transcriptome and genomic data (Fu et al, 2020). The downregulation of CPT2 can induce the suppression of fatty acid β‐oxidation to increase IMF accumulation (Fujiwara et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The most significant SNP found resides in a splice site in ACACA, which catalyzes the rate-limiting step in fatty acid biosynthesis through the carboxylation of acetyl CoA to malonyl-CoA. Gene expression levels and genetic markers of ACACA have been associated with fatness traits in pigs (Gallardo et al 2009;Eusebi et al 2017;Fu et al 2020;Pi orkowska et al 2020). Hypothalamic malonyl-CoA is implicated in food intake and (Schneider 2004;Zhuo et al 2014;McIlwraith & Belsham 2020) and human age at menarche (Speliotes et al 2010;Day et al 2015;Howard & Dunkel 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Other noteworthy genes in the study included Titin and TEK (angiopoietin-1 receptor known also as a tyrosine-protein kinase), which appeared to be under substantial multigene regulation and also were located close to significant splicing cis-regulatory SNP. In another study, Fu et al (2020) combined gene expression with GWAS and quantitative trait expression profiles to refine 180 candidate genes for fat-related traits down to just six, including known master regulators such as several PPARs (PPARG, PPARD and PPARA). New insights have been gained on the molecular pathways underpinning heterosis and its implications for growth, development and meat quality in sheep meat using RNA sequencing (Cheng et al, 2020).…”
Section: Genetic Regions and Gene Expression Associated With Meat Qua...mentioning
confidence: 99%